Optimizing Total Quality Management (TQM) Principles as a Strategy for Educational Transformation Towards the Golden Generation 2045 - Ardianti, Vika; Sumiatun, Sumiatun; Mustiningsih, Mustiningsih; Rochmawati, Rochmawati; Camara, Jun Solver (Journal of Education for Sustainability and Diversity, 2024)
Improving the quality of education is needed by developing human resources as an effort to prepare a superior generation of 2045, one of which is by paying attention to the implementation of TQM principles in schools. TQM is a management approach for an organization centered on quality, which is one of the keys to the success of the most effective educational goals to improve school quality. The purpose of this study is to provide an overview of how the golden generation 2045 and its challenges, educational transformation strategies and optimization of TQM principles. The research was conducted using the Systematic Literature Review (SLR) method. Researchers collected some literature in various scientific journals that were in accordance with the topic or discussion on Google Scholar with the Publish or Perish application and Science Direct. The results of this study found that the application of TQM principles has been quite well implemented by most schools, especially secondary education.